Monolithic refractory composition, monolithic refractory, method for manufacturing monolithic refractory, and inorganic binder
Patent Information
- Application Number
- JP2023128887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
AI Technical Summary
【0008】 本開示によれば、高い耐爆裂性を有する施工体が得られる不定形耐火組成物、不定形耐火物、不定形耐火物の製造方法、及び無機結合剤が提供される。
Smart Images

Figure 2025024632000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a monolithic refractory composition, a monolithic refractory, a method for making a monolithic refractory, and an inorganic binder. [Background technology]
[0002] Low cement castables are cements that have dramatically improved heat resistance and corrosion resistance compared to conventional cement castables. Monolithic refractories are constructed by adding water to low-cement castables, molding them, and then heating and drying them. However, when the temperature is raised, the free water inside the construction body turns into steam, increasing the water vapor pressure inside the construction body, and if the water vapor pressure exceeds the construction body's strength, the construction body will explode. In particular, low-cement castables require less water to be added compared to conventional cement castables, and the construction body's structure tends to be dense, making it more susceptible to explosions, so more strict management is required.
[0003] Patent Document 1 discloses an amorphous refractory composition that contains silicon carbide, aluminum lactate, and organic fibers, and that maintains excellent thermal conductivity and is resistant to explosion even when heated rapidly. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-101285 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in order to shorten construction periods, etc., there is a further demand for construction structures that are less likely to explode even when subjected to more rapid temperature increases and have high explosion resistance.
[0006] The present disclosure has been made in consideration of the above, and relates to an amorphous refractory composition, an amorphous refractory, a method for producing an amorphous refractory, and an inorganic binder that can provide a construction having high explosion resistance. [Means for solving the problem]
[0007] Specific means for solving the above problems include the following aspects. <1> Contains a refractory aggregate and an inorganic binder, The inorganic binder contains CaO·Al2O3, and the content of the CaO·Al2O3 in the inorganic binder is 55 mass% or more. Amorphous refractory composition. <2> The inorganic binder is an alumina cement; <1> The amorphous refractory composition according to claim 1. <3> The content of the inorganic binder is 1% by mass to 15% by mass based on the total mass of the amorphous refractory composition. <1> or <2> The amorphous refractory composition according to claim 1. <4> Further containing aluminum lactate, <1> ~ <3> 10. The amorphous refractory composition according to claim 9, <5> The content of the aluminum lactate is 0.1% by mass to 0.9% by mass based on the total mass of the amorphous refractory composition. <4> The amorphous refractory composition according to claim 1. <6> Further containing organic fibers, <1> ~ <5> The amorphous refractory composition according to claim 1. <7> The content of the organic fiber is 0.005% by mass to 0.7% by mass based on the total mass of the amorphous refractory composition. <6> The amorphous refractory composition according to claim 1. <8> The refractory aggregate contains at least one of alumina and silica. <1> ~ <7> 10. The amorphous refractory composition according to claim 9, <9> The content of the refractory aggregate is 60% by mass to 90% by mass based on the total mass of the amorphous refractory composition. <1> ~ <8> 10. The amorphous refractory composition according to claim 9, <10> It also contains bentonite. <1> ~ <9> 10. The amorphous refractory composition according to claim 9, <11> Further containing a dispersant, <1> ~ <10> 10. The amorphous refractory composition according to claim 9, <12> Further containing refractory powder, <1> ~ <11> 10. The amorphous refractory composition according to claim 9, <13> Used in the manufacture of unshaped refractories, <1> ~ <12> 10. The amorphous refractory composition according to claim 9, <14> <1> ~ <13> An amorphous refractory produced from the amorphous refractory composition described in any one of the above. <15> <1> ~ <13> A method for producing an amorphous refractory material, comprising: adding water to the amorphous refractory composition described in any one of the above items; molding the amorphous refractory composition to which water has been added; and drying the molded amorphous refractory composition. <16> An inorganic binder having a CaO·Al2O3 content of 55 mass% or more, used in a monolithic refractory composition for the production of monolithic refractories. Effect of the Invention
[0008] According to the present disclosure, there are provided an amorphous refractory composition, an amorphous refractory, a method for producing an amorphous refractory, and an inorganic binder that can provide a construction having high explosion resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] An embodiment of the present disclosure will be described in detail below. However, the present disclosure is not limited to the following embodiment. In the following disclosure, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to numerical values and their ranges, and do not limit the present disclosure. In the present disclosure, a numerical range indicated using "to" includes the numerical values before and after "to" as the lower limit and upper limit, respectively. In the present disclosure, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit of the numerical range may be replaced with a value shown in the examples. In the present disclosure, when a composition contains multiple substances corresponding to each component, the content of each component in the composition means the total content of the multiple substances present in the composition, unless otherwise specified.
[0010] ≪Amorphous refractory composition≫ The monolithic refractory composition of the present disclosure contains a refractory aggregate and an inorganic binder, the inorganic binder containing CaO·Al2O3, and the content of CaO·Al2O3 in the inorganic binder is 55 mass% or more.
[0011] In this disclosure, the term "unshaped refractory composition" refers to the entire powder before water is added. The term "unshaped refractory material" refers to a material obtained by adding water to an unshaped refractory composition, molding, and drying. The term "constructed body" includes a material in the middle of construction and an unshaped refractory material obtained by construction.
[0012] The structure obtained by using the moldable fireproof composition of the present disclosure has high explosion resistance. The function of the moldable fireproof composition of the present disclosure is not clear, but is presumed to be as follows. Water inside the application body exists as free water or structural water. Free water is water added to the unformed fireproof composition that does not undergo a hydration reaction and exists inside the application body as liquid water (i.e., H2O). Since the boiling point of water is 100°C, when the application body is heated to dry it, the water vapor pressure due to the free water inside the application body rises rapidly at around 100°C, making the application body prone to explosion. On the other hand, structural water is water that is added to the monolithic refractory composition and undergoes a hydration reaction with CaO·Al2O3, and exists inside the structure as a hydrate (for example, CaO·Al2O3·10H2O, etc.). Since the hydrate gradually decomposes at temperatures above 350°C, the water vapor pressure inside the structure does not rise suddenly when the structure is heated to dry it, and the structure is less likely to explode. Since the inorganic binder contained in the amorphous refractory composition disclosed herein has a high CaO·Al2O3 content of 55 mass% or more, it is presumed that the water added to the amorphous refractory composition easily becomes structural water inside the composition through a hydration reaction with CaO·Al2O3 when the temperature is raised, and since CaO·Al2O3, which has excellent compressive strength, can improve the strength of the amorphous refractory material, the occurrence of explosions when the temperature is raised rapidly can be suppressed. From the above, the construction body obtained from the unshaped fireproof composition of the present disclosure can be rapidly heated, and the construction period can be shortened. Note that the present disclosure is not limited to the above-mentioned assumed mechanism.
[0013] <Refractory aggregate> The castable refractory composition of the present disclosure contains refractory aggregate. In the present disclosure, the particle size of the "refractory aggregate" is 10 μm or more and 10 mm or less from the viewpoint of functioning as an aggregate. In the present disclosure, the particle size of the refractory aggregate can be measured by a sieving test in accordance with JIS Z 8815:1994, and is the particle size at which the cumulative volume is 50%. The "refractory aggregate" in the present disclosure and the "refractory powder" described later are distinguished by the difference in particle size.
[0014] The refractory aggregate is not particularly limited as long as it can be used to manufacture a monolithic refractory material. The monolithic refractory composition of the present disclosure may contain two or more types of refractory aggregate. The refractory aggregate preferably contains at least one element selected from the group consisting of aluminum, silicon, chromium, zirconium, magnesium, boron, and carbon. The refractory aggregate is more preferably at least one selected from the group consisting of alumina, high-purity alumina, bauxite, diaspore, mullite, kyanite, aluminium shale, chamotte, silica, silica stone, pyrophyllite, sillimanite, andalusite, chromite, spinel, magnesia, zirconia, zircon, chromia, silicon nitride, aluminum nitride, silicon carbide, boron carbide, carbon such as graphite, titanium boride, and zirconium boride. The Al2O3 content in high purity alumina is 90 mass% or more, the Al2O3 content in bauxite is 80 to 89 mass%, the Al2O3 content in mullite is around 60 mass%, and the Al2O3 content in chamotte is 40 to 50 mass%.
[0015] The refractory aggregate is preferably a silica-alumina-based raw material. The silica-alumina-based raw material is a refractory raw material mainly composed of silica and / or alumina. That is, the refractory aggregate is preferably at least one selected from the group consisting of alumina, high-purity alumina, bauxite, diaspore, mullite, kyanite, alumina shale, chamotte, silica, silica stone, pyrophyllite, sillimanite, andalusite, spinel, zircon, silicon nitride, aluminum nitride, and silicon carbide.
[0016] From the viewpoint of improving the explosion resistance, the content of the refractory aggregate is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 70% by mass or more, based on the total mass of the amorphous refractory composition. The content of the refractory aggregate is preferably 90% by mass or less, more preferably 87% by mass or less, and even more preferably 85% by mass or less, based on the total mass of the amorphous refractory composition.
[0017] <Inorganic binder> The moldable refractory composition of the present disclosure contains an inorganic binder. The inorganic binder is not particularly limited as long as it can be used to manufacture a monolithic refractory. The monolithic refractory composition of the present disclosure may contain two or more inorganic binders.
[0018] The content of the inorganic binder is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the total mass of the amorphous refractory composition. The content of the inorganic binder is preferably 15% by mass or less, more preferably 14% by mass or less, and even more preferably 13% by mass or less, based on the total mass of the amorphous refractory composition.
[0019] The inorganic binder of the present disclosure includes CaO·Al2O3. Alumina cement is preferred as the inorganic binder because it can maintain the strength of the manufactured monolithic refractory over a wide temperature range from room temperature to high temperatures. Alumina cement is a cement that contains CaO·Al2O3.
[0020] The content of CaO·Al2O3 is 55 mass% or more based on the total mass of the inorganic binder. From the viewpoint of improving the rapid heating suitability and improving the explosion resistance, the content of CaO·Al2O3 is preferably 60 mass% or more, more preferably 65 mass% or more, even more preferably 80 mass% or more, particularly preferably 90 mass% or more, most preferably 95 mass% or more, and may be 100 mass%. From the viewpoint of cost, the content of CaO·Al2O3 is preferably 99 mass% or less, based on the total mass of the inorganic binder.
[0021] As described above, the content of the inorganic binder relative to the total mass of the amorphous refractory composition is preferably 1 mass% to 15 mass%, and the content of CaO·Al2O3 relative to the total mass of the inorganic binder is 55 mass% or more. In the present disclosure, it is preferable to determine the content of the inorganic binder relative to the total mass of the amorphous refractory composition after specifying the content of CaO·Al2O3 relative to the total mass of the inorganic binder as 55 mass% or more, rather than only specifying the content of CaO·Al2O3 relative to the total mass of the amorphous refractory composition. For example, if the content of CaO·Al2O3 relative to the total mass of the inorganic binder is less than 55 mass%, the content of the inorganic binder relative to the total mass of the amorphous refractory composition will be increased in order to ensure the content of CaO·Al2O3 relative to the total mass of the amorphous refractory composition, which leaves little room for the amorphous refractory composition to contain components other than the inorganic binder, and the amorphous refractory composition of the present disclosure cannot be obtained.
[0022] The inorganic binder may contain components other than CaO·Al2O3, such as 12CaO·7Al2O3, CaO·2Al2O3, CaO·Al2O·CaSO4, CaO·Al2O3·Fe2O3, CaO·Al2O3·CaF2, and CaO·Na2O·Al2O3. From the viewpoint of improving the rapid heating suitability and improving the explosion resistance, the content of components other than CaO·Al2O3 is preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less, based on the total mass of the inorganic binder. Note that it is particularly preferable that no components other than CaO·Al2O3 are contained.
[0023] <Aluminum lactate> The moldable refractory composition of the present disclosure preferably contains aluminum lactate. The aluminum lactate is not particularly limited as long as it can be used to produce a monolithic refractory material. The monolithic refractory composition of the present disclosure may contain two or more types of aluminum lactate. Examples of aluminum lactate include normal aluminum lactate represented by Al(OCOCH(OH)CH3)3, basic aluminum lactate represented by Al(OH)(OCOCH(OH)CH3)2 or Al(OH)2(OCOCH(OH)CH3), and hydrates thereof. Among the above, the aluminum lactate preferably includes at least one selected from the group consisting of basic aluminum lactate and a hydrate of basic aluminum lactate. As aluminum lactate, a complex salt with citric acid, glycolic acid, or the like may be used.
[0024] From the viewpoint of improving the breathability of the monolithic refractory, the content of aluminum lactate is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.3% by mass or more, based on the total mass of the monolithic refractory composition. From the viewpoint of improving the strength of the monolithic refractory, the content of aluminum lactate is preferably 0.9% by mass or less, more preferably 0.8% by mass or less, and even more preferably 0.7% by mass or less, based on the total mass of the monolithic refractory composition. By setting the content of aluminum lactate to 0.1% by mass or more, the rapid temperature rise suitability can be further improved, and by setting the content of aluminum lactate to 0.9% by mass or less, the occurrence of curing shrinkage cracks in the monolithic refractory produced using the monolithic refractory composition of the present disclosure can be further suppressed.
[0025] <Organic fiber> The moldable refractory composition of the present disclosure preferably contains organic fibers. The organic fiber is not particularly limited as long as it can be used to manufacture a monolithic refractory material. The monolithic refractory composition of the present disclosure may contain two or more kinds of organic fibers. The type of organic fiber is not particularly limited, and at least one selected from the group consisting of polypropylene fiber, polyethylene fiber, polyester fiber, polyvinyl alcohol fiber, and cellulose fiber is preferable. Among these, the organic fiber is preferably polypropylene fiber from the viewpoint of suitability for rapid temperature rise.
[0026] The fiber length of the organic fiber is preferably 10 μm or more, more preferably 100 μm or more, and even more preferably 1.0 mm or more. The fiber length of the organic fiber is preferably 20 mm or less, more preferably 15 mm or less, and even more preferably 10 mm or less. When the fiber length of the organic fiber is 10 μm or more, the suitability for rapid temperature rise can be further improved. By making the fiber length of the organic fibers 20 mm or less, the transportability by an air current transport type spray machine when spraying the amorphous refractory composition can be further improved. The moldable refractory composition of the present disclosure may contain two or more types of organic fibers having different fiber lengths. In the present disclosure, the fiber length is measured in accordance with JIS L 1015:2010.
[0027] The fineness of the organic fiber is preferably 0.1 dtex or more, more preferably 0.5 dtex or more, and even more preferably 1 dtex or more. The fineness of the organic fiber is preferably 20 dtex or less, more preferably 15 dtex or less, and even more preferably 10 dtex or less. When the fineness of the organic fiber is 0.1 dtex or more, the suitability for rapid temperature rise can be further improved. By making the fineness of the organic fibers 20 dtex or less, the transportability by an air current transport type spray machine can be further improved when spraying the amorphous fireproof composition. In the present disclosure, the fineness is measured in accordance with JIS L 1015:2010.
[0028] From the viewpoint of improving the breathability of the monolithic refractory, the content of the organic fiber is preferably 0.005% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and particularly preferably 0.1% by mass or more, based on the total mass of the monolithic refractory composition. From the viewpoint of improving the strength of the monolithic refractory, the content of the organic fiber is preferably 0.7% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.4% by mass or less, and particularly preferably 0.3% by mass or less, based on the total mass of the monolithic refractory composition. By setting the content of organic fibers to 0.005% by mass or more, the suitability for rapid temperature rise can be further improved. By setting the content of organic fibers to 0.7% by mass or less, the transportability by an air current transport type spray machine when spraying the amorphous refractory composition can be further improved.
[0029] <Bentonite> The moldable refractory composition of the present disclosure preferably contains bentonite. Bentonite is a weakly alkaline clay rock whose main component is the clay mineral montmorillonite. Bentonite may also contain silicate minerals such as quartz, α-cristobalite, and opal as secondary components. Bentonite may also be accompanied by silicate minerals such as feldspar, mica, and zeolite, carbonate minerals such as calcite, dolomite, and gypsum, sulfate minerals, and sulfide minerals such as pyrite.
[0030] The content of bentonite is preferably 0.5% by mass or more, more preferably 0.8% by mass or more, and even more preferably 1% by mass or more, based on the total mass of the amorphous refractory composition. The content of bentonite is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, based on the total mass of the amorphous refractory composition. By making the bentonite content 0.5 mass % or more, dust generation during spraying can be reduced. By setting the bentonite content to 5 mass % or less, the strength, corrosion resistance, and transportability by an air current transport type spray machine of the monolithic refractory produced using the monolithic refractory composition can be further improved.
[0031] From the viewpoint of rapid setting action, the particle size of the bentonite is preferably 45 μm or less, and more preferably 10 μm or less. The particle size of the bentonite may be 1 μm or more. In the present disclosure, the particle size of bentonite can be measured by a laser diffraction particle size distribution measurement method in accordance with JIS Z 8825:2013, and is the particle size at which the cumulative volume is 50%.
[0032] <Dispersant> The moldable refractory composition of the present disclosure preferably contains a dispersant. The dispersant is not particularly limited as long as it can be used in the production of a monolithic refractory. The monolithic refractory composition of the present disclosure may contain two or more dispersants. The type of dispersant is not particularly limited, and is preferably at least one selected from the group consisting of phosphoric acid-based dispersants, carboxylic acid-based dispersants, and sulfonic acid-based dispersants. Phosphate-based dispersants include condensed phosphates such as sodium tripolyphosphate, sodium tetrapolyphosphate, and sodium hexametaphosphate. Carboxylic acid-based dispersants include polycarboxylates and polyacrylates. Examples of sulfonic acid dispersants include melamine sulfonate and β-naphthalene sulfonate.
[0033] The content of the dispersant is preferably 0.05% by mass or more, more preferably 0.06% by mass or more, and even more preferably 0.07% by mass or more, based on the total mass of the amorphous refractory composition. The content of the dispersant is preferably 0.5% by mass or less, more preferably 0.4% by mass or less, and even more preferably 0.3% by mass or less, based on the total mass of the amorphous refractory composition. By setting the content of the dispersant to 0.05% by mass or more, the strength and corrosion resistance of the monolithic refractory produced using the monolithic refractory composition can be further improved. By setting the content of the dispersant to 0.5 mass % or less, the long-term curing properties can be further improved.
[0034] <Refractory powder> The amorphous refractory composition of the present disclosure preferably contains a refractory powder. In the present disclosure, the particle size of the "refractory powder" is less than 10 μm. In the present disclosure, the particle size of the refractory powder can be measured by a laser diffraction particle size distribution measurement method in accordance with JIS Z 8825:2013, and is the particle size at which the cumulative volume becomes 50%.
[0035] The type of refractory powder is not particularly limited as long as it can enter the gaps between the refractory aggregates and bond the refractory aggregates together. The amorphous refractory composition of the present disclosure may contain two or more types of refractory powder. The refractory powder is preferably at least one selected from the group consisting of alumina, titania, bauxite, diaspore, mullite, aluminium shale, chamotte, pyrophyllite, sillimanite, andalusite, silica, chromite, spinel, magnesia, zirconia, zircon, chromia, silicon nitride, aluminum nitride, silicon carbide, boron carbide, titanium boride, zirconium boride, and amorphous silica such as silica. The above-mentioned materials may be used in the form of a colloid in which all or a part of them is dispersed in a liquid.
[0036] The content of the refractory powder is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more, based on the total mass of the amorphous refractory composition. The content of the refractory powder is preferably 24% by mass or less, more preferably 22% by mass or less, and even more preferably 20% by mass or less, based on the total mass of the amorphous refractory composition. By setting the content of the refractory powder to 1 mass % or more, the strength and corrosion resistance of the monolithic refractory material produced using the monolithic refractory composition can be further improved. By setting the content of the refractory powder to 24% by mass or less, dust generation during spraying of the amorphous refractory composition can be reduced, and transportability by an air current transport type spray machine can be further improved.
[0037] <Additives> The moldable refractory composition of the present disclosure may contain additives other than the above-mentioned components. Additives include antioxidants, shrinkage relaxants, and thickeners.
[0038] The above-described moldable refractory composition of the present disclosure is used to manufacture a moldable refractory. In the present disclosure, the monolithic refractory may be produced by any of spraying, pouring, or casting.
[0039] ≪Unshaped refractories≫ The monolithic refractory of the present disclosure is produced from the above-mentioned monolithic refractory composition. In the present disclosure, the production of the castable refractory composition may be carried out by any of spray application, pouring application, and casting application.
[0040] <Manufacturing method of unshaped refractory> The method for producing an amorphous refractory material disclosed herein includes adding water to the amorphous refractory composition, molding the amorphous refractory composition to which water has been added, and drying the molded amorphous refractory composition.
[0041] <Dry mixing> The method for producing the monolithic refractory of the present disclosure may include dry kneading the monolithic refractory composition before the kneading described below. The method for dry kneading is not particularly limited.
[0042] <Addition of water> The method for producing a monolithic refractory material according to the present disclosure includes adding water to a monolithic refractory composition. The method for adding water is not particularly limited.
[0043] In the method for producing an amorphous refractory material disclosed herein, it is preferable to add 1 part by mass to 20 parts by mass of water per 100 parts by mass of the amorphous refractory composition, it is more preferable to add 3 parts by mass to 15 parts by mass of water per 100 parts by mass of the amorphous refractory composition, and it is even more preferable to add 5 parts by mass to 13 parts by mass of water per 100 parts by mass of the amorphous refractory composition.
[0044] <Mixing> The method for producing the monolithic refractory of the present disclosure may include kneading the monolithic refractory composition with added water. The kneading method is not particularly limited as long as the amorphous refractory composition and water are mixed homogeneously. For kneading, an Omni mixer, a paddle mixer, a Nauta mixer, an Eirich mixer, a vortex mixer, a continuous kneader, or the like can be used.
[0045] In the kneading, in addition to the amorphous refractory composition and water, a pH adjuster, a surfactant, a defoamer, or the like may be kneaded together.
[0046] <Molding> The method of making a moldable refractory of the present disclosure includes forming a moldable refractory composition to which water has been added. In the manufacturing method of the monolithic refractory material disclosed herein, the molding method may be any of spraying, pouring, and casting. The above-mentioned unshaped refractory composition is suitable for spray application, and from the viewpoint of shortening the construction period, it is preferable that the molding is carried out by spray application.
[0047] (Spray application) The spray application involves spraying the above-mentioned castable fireproof composition onto a substrate (i.e., an object to be sprayed). In the spray application, application water may be added to the moldable fireproof composition before spraying it onto the object to be applied. From the viewpoint of application property, the application water is preferably water. The spray application may be either a dry spray application or a wet spray application.
[0048] An example of spray application will be described below. The spray construction device includes an air current conveyor, a conveying pipe, a construction water adding means, a construction water adding section, a spray nozzle, and a compressor.
[0049] The air current conveying machine uses compressed air from a compressor to transport the powdered amorphous refractory composition into a conveying pipe at a predetermined solid / gas ratio, and the transported amorphous refractory composition is further transported from one end of the conveying pipe (the air current conveying machine side) to the other end (the spray nozzle side).
[0050] The compressor supplies compressed air to the air conveyor. The amorphous refractory composition is transported in a transport pipe of the air transport machine by compressed air supplied from a compressor.
[0051] The amorphous refractory composition fed into the conveying pipe is conveyed within the conveying pipe in the direction of the spray nozzle by compressed air supplied to the air conveying machine.
[0052] The conveying pipe is a passage for conveying the powdered amorphous refractory composition to the spray nozzle by compressed air. Furthermore, even if application water is added to the amorphous refractory composition during transportation and the amorphous refractory composition becomes wet, the amorphous refractory composition can be transported to the spray nozzle by the compressed air.
[0053] The application water adding means adds application water into the transport pipe in which the powdered amorphous refractory composition is transported, thereby moistening the amorphous refractory composition. The wetted amorphous refractory composition is transported to a spray nozzle by compressed air from an air transport machine.
[0054] The spray nozzle is attached to the tip of the transport pipe and sprays the amorphous refractory composition to which application water has been added onto the object to be treated. The compressed air used for transport is deaerated into the outside air by the impact when it is sprayed onto the workpiece. The sprayed unshaped refractory composition rapidly coagulates after deaeration, and then hardens to become an unshaped refractory, forming a strong furnace wall. Forms, etc. may be used as necessary when manufacturing the unshaped refractory.
[0055] <Curing> The method of making a moldable refractory of the present disclosure may include curing the shaped moldable refractory composition. The curing may be any method such as natural curing (i.e., room temperature curing), moist curing (i.e., water sprinkling curing), steam curing, heated curing, autoclave curing, or spray curing.
[0056] <Drying> The method for producing the moldable refractory of the present disclosure includes drying the molded moldable refractory composition. The drying method is not particularly limited, but the temperature rise rate is preferably 40° C. / hour to 80° C. / hour, more preferably 50° C. / hour to 70° C. / hour, and even more preferably 60° C. / hour. Drying is preferably performed by raising the temperature to 400° C. to 800° C., more preferably 500° C. to 700° C., and even more preferably up to 600° C. More specifically, the drying is preferably performed by increasing the temperature up to 600° C. at a rate of 60° C. / hour (that is, the drying time is 10 hours).
[0057] <Inorganic binder> The inorganic binder having a CaO·Al2O3 content of 55 mass % or more according to the present disclosure is used in a monolithic refractory composition for producing a monolithic refractory. The explanations regarding the inorganic binder having a CaO·Al2O3 content of 55 mass% or more, the production of amorphous refractory material, and the amorphous refractory composition of the present disclosure, including definitions, examples, and preferred aspects, are the same as the explanations of the above-mentioned <Inorganic binder>, <<Production method of amorphous refractory material>>, and <<Amorphous refractory composition>>, respectively. EXAMPLES
[0058] Examples of the present disclosure will be described in more detail below, but the present disclosure is not limited to the following examples as long as they do not deviate from the gist of the disclosure. Example 1 is a comparative example, and Examples 2 to 9 are working examples.
[0059] (Example 1 to Example 9) Monolithic fireproof compositions were prepared by mixing various components according to the ratio shown in Table 1. In Table 1, the unit of the numerical value of each component is parts by mass, and "-" indicates that the component was not mixed. Details of the various components shown in Table 1 are as follows: Refractory aggregate: Mullite (i.e., silica-alumina-based raw material in this disclosure) Bentonite: particle size less than 10μm Refractory powders other than those mentioned above (i.e. refractory powders other than refractory aggregates and bentonite, with a particle size of less than 10 μm): alumina, silica Dispersant: Sodium tripolyphosphate Aluminum lactate: Basic aluminum lactate Organic fiber: Polypropylene fiber Inorganic binder A: Alumina cement with a CaO·Al2O3 content of 52% by mass Inorganic binder B: Alumina cement with a CaO·Al2O3 content of 65 mass% Inorganic binder C: Alumina cement with a CaO·Al2O3 content of 74 mass% Inorganic binder D: Alumina cement with a CaO·Al2O3 content of 84 mass% Inorganic binder E: Alumina cement with a CaO·Al2O3 content of 99% by mass
[0060] <Rapid heating suitability evaluation> 10,000 g of each of the amorphous refractory compositions prepared in Examples 1 to 9 was dry-kneaded for 1 minute, and then 1,000 g of water was appropriately added and kneaded for 3 minutes to obtain a kneaded mixture. The kneaded mixture was then thrust into a cylindrical mold with a height of 100 mm and a diameter of 100 mm to prepare two cylindrical test specimens for each sample. After curing for 24 hours in a 20°C environment, the refractory was placed in an electric furnace with a 1400°C atmosphere and removed after 30 minutes to obtain a monolithic refractory. The monolithic refractory was visually observed for the presence or absence of explosion, and its rapid heating suitability was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) A: No explosion was observed in the unshaped refractories. B: One explosion site was found in the unshaped refractory. C: Two or more explosion sites were observed in the monolithic refractory, and there was a problem with its suitability for rapid heating.
[0061] <Bending strength evaluation> 10,000 g of each of the amorphous refractory compositions prepared in Examples 1 to 9 was dry-kneaded for 1 minute, and then 1,000 g of water was appropriately added and kneaded for 3 minutes to obtain a kneaded mixture. The kneaded mixture was then inserted into a 160 mm x 40 mm x 40 mm mold to prepare three rectangular parallelepiped specimens for each sample. After curing for 24 hours in an environment at 20°C, the molded refractory was dried for 24 hours at 110°C to obtain a molded refractory. The bending strength (unit: MPa) of the molded refractory was measured by a castable refractory strength test conforming to JIS R 2553:1992. Furthermore, the bending strength was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) A: The bending strength of the monolithic refractory was 6.0 MPa or more. B: The bending strength of the monolithic refractory was 5.0 MPa or more and less than 6.0 MPa. C: The bending strength of the monolithic refractory was less than 5.0 MPa.
[0062] [Table 1]
[0063] From the above, in Examples 2 to 9, the moldable fireproof compositions were obtained that were excellent in the rapid heating suitability evaluation, that is, capable of giving applied articles having high explosion resistance.
Claims
1. Contains a refractory aggregate and an inorganic binder, The inorganic binder is CaO.Al 2 O 3 The inorganic binder contains CaO.Al. 2 O 3 The content of is 55% by mass or more, Amorphous refractory composition.
2. 2. The castable refractory composition of claim 1, wherein the inorganic binder is an alumina cement.
3. The amorphous refractory composition according to claim 1 or claim 2, wherein the content of the inorganic binder is 1% by mass to 15% by mass relative to the total mass of the amorphous refractory composition.
4. The amorphous refractory composition according to claim 1 or 2, further comprising aluminum lactate.
5. The amorphous refractory composition according to claim 4, wherein the content of the aluminum lactate is 0.1% by mass to 0.9% by mass based on the total mass of the amorphous refractory composition.
6. The amorphous refractory composition according to claim 1 or 2, further comprising organic fibers.
7. The amorphous refractory composition according to claim 6, wherein the content of the organic fibers is 0.005% by mass to 0.7% by mass relative to the total mass of the amorphous refractory composition.
8. The amorphous refractory composition according to claim 1 or 2, wherein the refractory aggregate contains at least one of alumina and silica.
9. The amorphous refractory composition according to claim 1 or claim 2, wherein the content of the refractory aggregate is 60% by mass to 90% by mass relative to the total mass of the amorphous refractory composition.
10. The amorphous refractory composition according to claim 1 or 2, further comprising bentonite.
11. The amorphous refractory composition according to claim 1 or 2, further comprising a dispersant.
12. The amorphous refractory composition according to claim 1 or 2, further comprising a refractory powder.
13. The amorphous refractory composition according to claim 1 or 2, which is used for producing an amorphous refractory material.
14. A moldable refractory produced from the moldable refractory composition according to claim 1 or 2.
15. A method for producing an amorphous refractory material, comprising: adding water to the amorphous refractory composition described in claim 1 or claim 2; molding the amorphous refractory composition to which water has been added; and drying the molded amorphous refractory composition.
16. CaO.Al used in the monolithic refractory composition for the production of monolithic refractories 2 O 3 The inorganic binder has a content of 55 mass % or more.
Citation Information
Patent Citations
Castable refractory composition, castable refractory, and method of producing castable refractory
JP2022101285A